DEVELOPMENT OF FRAMEWORK FOR HIGH SCHOOL GEOGRAPHY CURRICULUM BASED ON ISLAMIC VALUES - Aniq Darajat; Ulil Amri Syafri; Ibdalsyah Ibdalsyah (Sekolah Tinggi Agama Islam Al Hidayah, 2020)
Throughout history, Geography has a special position in the life of a Muslim, so they feel the need to learn this knowledge, more than any other discipline. Unfortunately, Geography learning, especially in high schools ignoring these facts and then empty of its association with Islamic values. This paper seeks to formulate the initial steps to develop a high school Geography curriculum based on Islamic values. This research uses a library research approach. The steps taken in this study includes study of key concepts in Islamic education that can be used as an educational curriculum framework that is inline with Islamic values. Principles for the compilation of Islamic values based churriculum, among others. First, the objectives are aligned and are a translation of the objectives of Islamic education. Second, the content of the material includes and corresponds to Islamic educational material including the history of Geography, great cotibution of Muslim scholars, and geographical conditions of Muslim countries. It also should be free from material content that are not aligned with Islamic values. Third, the teaching method the teaching of science can no longer be separated from the teaching of revelation (al-Qur'an and as-Sunnah). It also provides learning experiences appropriate for moral and spiritual development by providing a balance between a student-centered and a subject-centered approach. Fourth, evaluation of education needs to pay attention to the achievement of the objectives of Islamic education, and not limited to aspects of knowledge, attitudes and skills but is empty of the achievement of ultimate educational goals.